Comparison of HPV testing and cervical cytology in prevention of cervical cancer - Klaudia Remjasz; Katarzyna Kosz; Aleksandra Kuchnicka; Julia Kuchnicka; Jakub Aleksandrowicz; Martyna Zielińska; Natalia Zarankiewicz; Wojciech Siedlecki; Klaudia Sapuła (Journal of Education, Health and Sport, 2022)
Introduction and purpose This article aims to compare two guiding methods of cervical cancer screening: cervical cytology and HPV testing. The objective is to provide information on which method is currently more relevant in the early detection of precancerous lesions.